(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Question: What is the current state of local Solorina populations in Ukraine? How many lichenicolous fungi are associated with this genus? Location: Ukraine. Materials and methods: field research, herbarium (KW-L) and database (GBIF) data, microscope technique. Nomenclature: https://www.indexfungorum.org/ Results: A critical revision was carried out for the lichen genus Solorina in Ukraine and allied lichenicolous fungi. The current state of their local populations was assessed. The subarctic-alpine species S. bispora, S. crocea, S. saccata and S. spongiosa are present in Ukraine. It is distributed in Carpathians, rare in Crimea and the plain part (Kremenetski Mts). Lichenicolous fungi Dacampia engeliana, Pyrenidium cf. actinellum, Scutula tuberculosa and Stigmidium solorinarium are found on Solorina saccata. The species S. solorinarium is the first time reported for Ukraine. Solorina saccata is represented in Ukraine by 11 local populations, distributed in the Carpathians (6 populations), Crimea (3 populations) and the Kremenets Mountains (1 population). Over the past five decades, the existence of a single local population has been corroborated on Chyvchyn Mt, while four new populations have been found in the Gorgany, Chyvchyn Mountains (Kukulyk Mountain), Kuziy-Trybushanskyi Massif, and Kremenets Mts. The existence of the other 6 local populations on Svydovets Mt, Bystrytsia Mt, Hoverla Mt in the Carpathians and on the Inzhesyrt Mt, Vesely Mt and in the upper reaches of the Alma River in Crimea has not been confirmed over the past 50 years. Solorina bispora is represented in Ukraine by 4 local populations on Petros Mt, Hoverla Mt, Svydovets Mt and Chyvchyn Mt, which have not been confirmed by research over the past 50 years. According to IUCN criteria, we classify it as “Regionally Extinct” (RE). Solorina spongiosa is known in Ukraine from four local populations. We confirmed the growth of S. spongiosa at the foot of Chyvchyn Mt after 90 years, and found a new population (Bryusnyi Polonyna Mt). The status of two local populations, one in the south of the Chyvchyn Mts (not found) and the other without an exact location in the Lviv region (not observed), is unknown. Solorina crocea has been known in Ukraine from a single local population on Pip Ivan Mt in the subalpine region for over 85 years. It is threatened with extinction under the influence of global climate change and, probably, recreational activities. To ensure its protection, we propose to include the species in the Red Book of Ukraine under the category “vulnerable” (VU).